IMPLEMENTATION OF DIFFERENTIATED LEARNING TO STUDENT LEARNING OUTCOMES IN ISLAMIC RELIGION SUBJECTS AT THE ELEMENTARY SCHOOL LEVEL - Muhamad Ihza Pramudya; Heny Narendrany Hidayati Heny Narendrany Hidayati (Amal Insani Foundation, 2023)
Learning differentiates the teacher's proactive plans through attention by providing various ways for students to be able to access knowledge by taking various approaches both in content, process, and product. Research objectives to determine the application of learning styles (visual, auditory, kinesthetic) to student learning outcomes. The type of research conducted was a literature review, with the intended subject being the elementary school level. The data analysis technique was carried out by going through four stages, namely data collection, data reduction, data presentation, and conclusion. The results of this research conceptually reveal that the method of implementing differentiated learning in the PAI subject is by first looking at the learning needs of students so that a teacher can map students according to their learning needs. In applying learning styles, a teacher must also adjust the material to be taught for example pilgrimage material, a teacher can share it by teaching it by showing PPT, sing songs, and in practice, to improve the quality of learning outcomes